CULTURA SERVICIILOR BIBLIOTECII PUBLICE ÎN ERA COMUNICĂRII ȘI DIGITIZĂRII - KULIKOVSKI, Conf. univ. dr, .director, Departamentul studii și cercetări, Lidia (BIBLIOPOLIS, 2020)
We are living in the world of services. The library by its mission is an institution that offers services. The article talks about the orientation of libraries to the new community services, which are the unique chance for the future. Without diminishing the known library services (loan, on-site loan, events etc.), which still exist and in the modern library, the author provides examples of new library roles, necessary for the new community services based on the technology and the individual interest of theirs community members, argumenting by the afirmations of specialists as Seth Godin, Tomas Frey, Neil Geyman etc. In a comprehensible manner, the author provides the definition of the term community services (creating value for anyone), insisting that the libraries will receive the profit by offering services to someone. The message of the article is a challenge - to infuse the passion for qualitative services and to delivery the principles of qualitative services in schools, in community, in libraries and to interlace into the each members of community lives. The education of culture of service in libraries is imperative. Along with this message challenge the author provides an overview of services based on the results of discussions with „B.P. Hasdeu” Municipal Library librarians. Together with this message the author provides a classification of services based on the discussions with the librarians of the B.P. Hasdeu Municipal Library.